On the mechanism of energy transduction in myosin subfragment 1. - Botts, J (1984)
It is proposed that the myosin subfragment 1 moiety of the muscle contractile apparatus is a self-contained "engine" whose operational plan is based on the interactive nature of ATP (or degradation intermediate) binding and actin binding, made possible by an intersite communication system. It is suggested that the spatial information required for examining this engine can, at least provisionally, be derived from fluorescence resonance energy transfer measurements interpreted by the Förster equation and that the existence of an intersite communication system can be deduced from piece-wise detection of interacting pairs of points.